Media and Internet Linguistics: Language Transformation in Digital Communication - Pirdaus, Dede Irman; Vera (Communication In Research And Publications, 2025)
This study examines the transformation of language form and function in digital communication, focusing on platforms such as Twitter, TikTok, Instagram, Reddit, and Kaskus. Through a qualitative-descriptive approach and multimodal analysis of 2,000 digital entries, it was found that digital communication forms a new language genre that is hybrid, visual, and performative. Phenomena such as code-mixing, acronyms, phonetic spelling, and the use of emoticons and memes reflect linguistic adaptations to the speed, efficiency, and emotional expression that characterize digital platforms. The findings show linguistic variation between generations: Gen Z tends to use visual symbols and concise language, while older generations (Millennials and Gen X) maintain a more formal sentence structure. Data visualization using NVivo and Voyant Tools strengthens the identification of dominant themes such as emotion, irony, and community slang. These findings support previous literature, such as Barrot (2022) and Kurmanbekova et al. (2023), which highlight the simplification and diversification of language in the digital era. This study confirms that social media is not only a space for linguistic expression, but also an arena for innovation, the spread of digital dialects, and shifts in communication norms. While bringing creativity and cultural engagement, these changes also raise concerns about the decline in formal literacy skills. Therefore, this study recommends further exploration of the long-term impact of digital language use on literacy education and culture.